the تنفيذ الخريطة الذهنية في تعلم إسم موصول فصل التاسع بمعهد دار الحكمة تنغيرانج: تنفيذ الخريطة الذهنية في تعلم إسم موصول فصل التاسع بمعهد دار الحكمة تنغيرانج - Dina Maulidina Dina Maulidina; Miatin Rachmawati (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2022)
A method in learning is an important thing that must be applied by an educator, especially in learning Arabic which has the notion that it is difficult to learn, especially Nahwu Science. In this study, researchers implemented the Mind Mapping method in learning Nahwu Science about Isim Maushul material for class IX students of Daarul Hikmah Islamic Boarding School Tangerang. This study aims to find out whether there is an influence between the methods applied to student learning outcomes. Researchers used a type of quantitative research method with an experimental model. The results showed that there was a significant influence between the Mind Mapping method and learning Nahwu Science. This can be proven through the results of the Paired sample t-test with a Sig. (2-tailed) 0.05, namely 0.000 <0.05 and the independent sample t-test with a sig (2-tailed) value of 0.03 <0.05, so there is an influence between variable X on variable Y. So it can be concluded that the implementation of the Mind Mapping method is effective to be